Analgesic effect of butorphanol tartrate combined with hydromorphone on patients with cesarean section: A prospective cohort study. Issue 48 (2nd December 2022) - Zhang, Ying; Xie, Shixuan; Zhang, Guanglei; Gong, Xun
Abstract : To evaluate the analgesic effect of butorphanol tartrate combined with hydromorphone on the patients with cesarean section, we conducted a prospective cohort study. A total of 90 patients were given patient-controlled intravenous analgesia (PCIA) with hydromorphone for 24 hours after the cesarean section. After stopping PCIA, they were divided into 2 groups randomly. The cases treated with butorphanol tartrate intravenous drip were evaluated as the butorphanol group (n = 45) and the cases treated with saline were evaluated as the control group (n = 45). We compared the vital signs, analgesic effect, adverse reactions, the bladder and gastrointestinal function recovery, and neonatal jaundice between the 2 groups. The visual analog score in butorphanol group was significantly lower than that of control group at 3 and 4 hours after stopping PCIA ( P  < .05), but there was no significant difference in visual analog score at 6 and 12 hours after stopping PCIA. The first time of getting out of bed and urination in butorphanol group was significantly later than that in control group while there was no significant difference in the first anal ventilation and the neonatal jaundice index between the 2 groups. We should pay attention to the pain of patients with cesarean section after stopping PCIA. The combination of butorphanol tartrate and hydromorphone play a good effect to relieve the pain while nursing care should be strengthened to urge patients to take early activities to reduce the occurrence of urinary retention.